2022
DOI: 10.3389/fcvm.2022.797137
|View full text |Cite
|
Sign up to set email alerts
|

ADAMTS8 Promotes Cardiac Fibrosis Partly Through Activating EGFR Dependent Pathway

Abstract: Myocardial infarction or pressure overload leads to cardiac fibrosis, the leading cause of heart failure. ADAMTS8 (A disintegrin and metalloproteinase with thrombospondin motifs 8) has been reported to be involved in many fibrosis-related diseases. However, the specific role of ADAMTS8 in cardiac fibrosis caused by myocardial infarction or pressure overload is yet unclear. The present study aimed to explore the function of ADAMTS8 in cardiac fibrosis and its underlying mechanism. ADAMTS8 expression was signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Signaling pathways include cytokine signaling in immune system [48], extracellular matrix organization [49], diseases of metabolism [50], hemostasis [51], innate immune system [52], metabolism of lipids [53] [87], CES1 [88], CYP19A1 [89], PLAC8 [90], CD36 [91], GIPR (gastric inhibitory polypeptide receptor) [92], ARG1 [93], MSR1 [94], DOCK2 [95], S1PR1 [96], OXTR (oxytocin receptor) [97], F11R [98], LEPR (leptin receptor) [99], AR (androgen receptor) [100], DKK3 [101], FOXO1 [102], PIK3CB [103], WWP1 [104], PHIP (pleckstrin homology domain interacting protein) [105], MPZL3 [106], FBXO2 [107], GUCY2C [108], ADRA2A [109], CHRNA5 [110], GLP2R [111], SDC3 [112], NFAT5 [113], PON2 [114], PRNP (prion protein) [115], DGKE (diacylglycerol kinase epsilon) [116], ARHGAP21 [117], COQ2 [118], EPHX2 [119] and FAM3C [120] were observed to be associated with the progression of obesity. Vargas-Alarcón et al [ [133], Jiang et al [134], Yu et al [135], Jiang et al [136], Huang et al [137], Scuruchi et al [138], Wang et al [139], Ibrahim et al [140], Zha et al …”
Section: Discussionmentioning
confidence: 99%
“…Signaling pathways include cytokine signaling in immune system [48], extracellular matrix organization [49], diseases of metabolism [50], hemostasis [51], innate immune system [52], metabolism of lipids [53] [87], CES1 [88], CYP19A1 [89], PLAC8 [90], CD36 [91], GIPR (gastric inhibitory polypeptide receptor) [92], ARG1 [93], MSR1 [94], DOCK2 [95], S1PR1 [96], OXTR (oxytocin receptor) [97], F11R [98], LEPR (leptin receptor) [99], AR (androgen receptor) [100], DKK3 [101], FOXO1 [102], PIK3CB [103], WWP1 [104], PHIP (pleckstrin homology domain interacting protein) [105], MPZL3 [106], FBXO2 [107], GUCY2C [108], ADRA2A [109], CHRNA5 [110], GLP2R [111], SDC3 [112], NFAT5 [113], PON2 [114], PRNP (prion protein) [115], DGKE (diacylglycerol kinase epsilon) [116], ARHGAP21 [117], COQ2 [118], EPHX2 [119] and FAM3C [120] were observed to be associated with the progression of obesity. Vargas-Alarcón et al [ [133], Jiang et al [134], Yu et al [135], Jiang et al [136], Huang et al [137], Scuruchi et al [138], Wang et al [139], Ibrahim et al [140], Zha et al …”
Section: Discussionmentioning
confidence: 99%
“…This study found that ADAMTS8 was upregulated in the myocardium of HF rats and ADAMTS8 overexpression counteracted the anti-inflammatory and antifibrotic effects of Yinxin granules. A recent study showed that ADAMTS8 partially promotes cardiac fibrosis by activating epidermal growth factor receptor-dependent pathways, 31) which provides insight into the function of ADAMTS8 in the myocardium. To date, the tumor-suppressive role of ADAMTS 8 has been extensively studied.…”
Section: Discussionmentioning
confidence: 99%
“…In our dataset, three different variants with uncertain significance have been identified in genes coding for MMPs (MMP24, ADAMTSL5, ADAMTSL8). ADAMTS8 expression was strongly increased in DCM, while in vitro studies evidenced its role into the activation of cardiac fibroblasts [ 64 ].…”
Section: Discussionmentioning
confidence: 99%